2004
DOI: 10.1126/science.1096566
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Hollow Nanocrystals Through the Nanoscale Kirkendall Effect

Abstract: We demonstrate that hollow nanocrystals can be synthesized through a mechanism analogous to the Kirkendall Effect, in which pores form due to the difference in diffusion rates between two components in a diffusion couple. Cobalt nanocrystals are chosen as a primary example to show that their reaction in solution with oxygen, sulfur or selenium leads to the formation of hollow nanocrystals of the resulting oxide and chalcogenides. This process provides a general route to the synthesis of hollow nanostructures o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

69
2,666
9
25

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 3,373 publications
(2,769 citation statements)
references
References 27 publications
69
2,666
9
25
Order By: Relevance
“…If edges dissolve, the trial fails. Etching the nanosphere would lead to hollow structure or yolk‐shell structure because of the different migration rate, this is so called Kirkendall effect 137. Regular NFs would be formed under suitable environment driving by Kirkendall effect.…”
Section: Novel Structures and Atypical Edgesmentioning
confidence: 99%
“…If edges dissolve, the trial fails. Etching the nanosphere would lead to hollow structure or yolk‐shell structure because of the different migration rate, this is so called Kirkendall effect 137. Regular NFs would be formed under suitable environment driving by Kirkendall effect.…”
Section: Novel Structures and Atypical Edgesmentioning
confidence: 99%
“…Generally, two main strategies, e.g., template‐based (hard‐ and soft‐templates) and template‐free (Kirkendall effect, galvanic replacement, and Ostwald ripening), are used to obtain well‐defined hollow spheres with different compositions and shapes 5, 10, 11, 12, 13, 14, 15, 16, 17. Recent researches have demonstrated that hollow spheres constructed with 1D nanorods/nanoneedles18 and 2D nanosheets19, 20, 21, 22 even exhibit faster surface reaction rates and better physicochemical stability because they occupy much larger specific surface areas than the most hollow spheres composed of 0D nanoparticles,23 and simultaneously inherit the characteristics of the constituent units.…”
Section: Introductionmentioning
confidence: 99%
“…Different methods have been developed to synthesize hollow nanostructures, 5−10 which include using sacrificing templates 2,11 by taking advantage of the Kirkendall effect 5−8 and the galvanic erosion. 12,13 Since the earlier work by Yin et al, 5 there have been many reports on the colloidal synthesis of hollow nanostructures by Kirkendall effects. 6,7,14−17 During a Kirkendall reaction, the different diffusivities of the atoms in a diffusion couple can induce supersaturation of vacancies at the interface, and the further condensation of excess vacancies and interdiffusion lead to the formation of a hollow nanoparticle.…”
mentioning
confidence: 99%
“…5,6,14,18 For instance, steady-state bulk diffusion has been proposed where the reaction species shuffling through the shell is assumed to be constant and uniformly distributed. 5 Surfacediffusion-mediated growth was also introduced in a number of experiments where a void is formed at the core/shell interface, and further growth of the void is controlled by the diffusion of reactants on the void surface. 8,14 Most of these models are based on ex situ observations.…”
mentioning
confidence: 99%